Using mobile-phone technology to change behaviour: Lessons from mNutrition - Barnett, Inka; Gordon, Jessica; Faith, Becky; Gilligan, Daniel O.; Hidrobo, Melissa; Palloni, Giordano; Batchelor, Simon; Scott, Nigel (United Nations Systems Standing Committee on Nutrition, 2020)
This article presents key lessons learned from a rigorous mixed-method evaluation of mNutrition, a global mobile phone-based advisory service that promotes behavioural change around key nutrition and farming practices to boost the nutritional health of children and adults in low-income countries. The evaluation found that the reach and sustained uptake of mobile mNutrition services remain a challenge among very poor households, with women often being excluded. mNutrition services currently have limited effect on nutrition and agriculture behaviours at scale, although active users (those users who adopted and engaged with the service) report some behavioural change. Still, well-designed mNutrition services can provide individually tailored, practical and context-specific advice that is often lacking from other information sources. Mobile phone-based advisory services alone tend to be insufficient to ensure uptake, engagement and behavioural change. In-person support features may help, but also raise the cost of the service.